Accompagner l'acculturation aux écrits universitaires : les cours de méthodologie du travail universitaire - Nathalie Gettliffe
Our research aims at understanding how different subject teachers of university methodology classes at the University of Strasbourg (France) try to help freshmen students to acquire the academic writing skills necessary to succeed in their subject. Ten teachers from eight departments were interviewed and courses' syllabi were analyzed. Even though university teachers are not specialists of academic writing they have designed their courses with similar components in order to lead students to enter the world of research (libraries), to train them to become autonomous learners, to make them understand academic content and its specific forms as well as to support them in their future professional lives. The strong link between subject and writing in these first year methodology classes suggests that it might be opportune to think about developing academic writing teaching through content while relying on university teachers from different subjects.